Exacerbated heat strain during consecutive days of repeated exercise sessions in heat - Pryor, R. R.; Pryor, J. L.; Vandermark, L. W.; Adams, E. L.; Brodeur, R. M.; Armstrong, L. E.; Lee, E. C.; Maresh, C. M.; Anderson, J. M.; Casa, D. J. (Journal of Science and Medicine in Sport, 2019)
Objectives: An exercise session in a hot environment may increase thermal strain during subsequent exercise sessions on the same and consecutive days. Therefore, this study was conducted to determine lasting physiological strain from moderate-high intensity, intermittent exercise in heat on subsequent exercise. Design: Repeated measures laboratory study. Methods: Seventeen healthy, recreationally active men (age: 22 ± 3 y, maximal oxygen consumption: 54.6 ± 5.3 mL kg-1 min-1) underwent two intermittent moderate-high intensity aerobic exercise sessions separated by 2 h of rest one day, followed by one session 24 h later in a 40 °C, 40% relative humidity environment. Heart rate, rectal temperature, heat stress perception, and environmental symptoms were assessed. Results: 100%, 35%, and 71% of participants completed the full exercise protocol during the first exercise session, second exercise session, and the following day, respectively. Exercising heart rate and rectal temperature were greater during the second exercise session (189 ± 11 bpm, 38.80 ± 0.47 °C) than the first identical exercise session (180 ± 17 bpm, p = 0.004; 38.41 ± 0.52 °C, p = 0.001), respectively. Immediate post-exercise heart rate, rectal temperature, thirst, thermal sensation, fatigue, and perceived exertion were similar among exercise sessions despite a shorter exercise duration during the second exercise session (93 ± 27 min, p = 0.001) and the following day (113 ± 12 min, p = 0.032) than the first exercise session (120 ± 0 min). Conclusions: Moderate-high-intensity intermittent exercise in the heat resulted in greater heat strain during a second exercise session the same day, and exercise the subsequent day.